2018
DOI: 10.1075/is.17040.lie
|View full text |Cite
|
Sign up to set email alerts
|

Mind the gap – moving beyond the dichotomy between intentional gestures and emotional facial and vocal signals of nonhuman primates

Abstract: Despite the variety of theories suggesting how human language might have evolved, very few consider the potential role of emotions in such scenarios. The few existing theories jointly highlight that gaining control over the production of emotional communication was crucial for establishing and maintaining larger social groups. This in turn resulted in the development of more complex social emotions and the corresponding sophisticated socio-cognitive skills to understand others’ communicative behavior, providin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 49 publications
1
16
0
Order By: Relevance
“…The study of intentional communication in non‐human animals started out as an endeavour in the gestural modality (Liebal & Oña, ). Tomasello et al .…”
Section: Cognitive Mechanisms Identified In Non‐human Gestures and Vomentioning
confidence: 99%
See 1 more Smart Citation
“…The study of intentional communication in non‐human animals started out as an endeavour in the gestural modality (Liebal & Oña, ). Tomasello et al .…”
Section: Cognitive Mechanisms Identified In Non‐human Gestures and Vomentioning
confidence: 99%
“…The study of intentional communication in non-human animals started out as an endeavour in the gestural modality (Liebal & Oña, 2018). Tomasello et al (1985) and used a Grice-inspired approach to develop criteria for potentially intentional communication in the gestural modality in great apes.…”
Section: (1) Intentionalitymentioning
confidence: 99%
“…More recently, voices in the field of primatology (Graham, Wilke, Lahiff, & Slocombe, 2019;Kret, Prochazkova, Sterck, & Clay, 2020;Liebal & Oña, 2018;Townsend et al, 2017) have returned to question again whether such a dichotomous view of primate communication is biologically meaningful and argue that instead, such views may hamper progress in understanding the proximate and ultimate explanations that shape primate signaling. Two fundamental problems are discussed; the first is that different signal components (i.e.…”
mentioning
confidence: 99%
“…Two fundamental problems are discussed; the first is that different signal components (i.e. vocal, facial, gestural) are still primarily studied in isolation rather than together as multimodal/multicomponent signal displays, despite the latter being more ecologically valid (Liebal & Oña, 2018; 5 Some scholars have suggested that our capacity for intentional emotion communication, paired with the evolution of greater emotional granularity in the way we construct emotional states (Feldman Barrett, 2017), laid the foundations for the evolution of language (Turner, 1996) as well as for hyper-cooperation and morality (Eisenberg, 2000).…”
mentioning
confidence: 99%
See 1 more Smart Citation